Caricom hotel market penetration project (Horwath & Horwath LondonGB, 1987)
Proposal for undertaking study to identify opportunities for increased use of local products within the CARICOM hotel sector and to establish an appropriate export market strategy. Proposal is set out under the following main headings; background to the study, comments on terms of reference, proposed approach, the consultants, proposed consulting team, and administration of the study.
IDS